The Role of Students In Facing The Challenges of The World of Work - Marbun, Jesiska; Ramadhani, Rani; Sembiring, Otnial (Asosiasi Dosen Akuntansi Indonesia, 2023)
It's definitely not an intellectual thing, but maybe it's not.Both hard skills and soft skills are competencies that have spiritual value.However, there are also challenges and problems which are called difficulties, obstacles, confusion, dissatisfaction, gaps, and so on.In the world of work, students experience challenges in studying and working.Students must be able to plan and manage their time well so that they can run without disrupting other activities or events.Therefore, problem solving is a scientific process that goes through the stages of understanding the problem, determining a solution, and searching for the information needed to evaluate the solution.This means that when facing a problem, you should first look for the root source of the problem.Makes it easier for someone to decide which solution to use to solve a problem.